My ECredit Banking Apps (MECBA) V3 / Wan Razazila Wan Abdullah (Dr) ... [et al.] - Wan Abdullah, Wan Razazila (Dr); Sutan Maruhun, Enny Nurdin (Dr); Nordin, Norzarina; Halid, Sunarti; Puteh Salin, Ahmad Saiful Azlin (Prof. Madya Dr) (2021)
Commercial banks are the major players in the banking system because they are the largest and most important suppliers of funds in the banking systems. The primary function of commercial banks is to provide retail banking services, such as accepting deposits, granting loans and advances, and financial guarantees. Basically, there are four (4) types of bank credit or loan available for customers to choose from; Simple Interest, Simple Interest with Compensating Balance, Discount Interest, and Discount Interest with Compensating Balance. Typically, the public is not aware of the best alternative. The best option is to choose the one with the lowest annual interest cost of the loan. This is known as an effective annual rate (EAR). However, not everyone knows how to calculate EAR. Hence, My eCredit Banking Apps (MECBA) V3 has been innovated to help the borrower to calculate the best interest rate and finance options provided by the commercial banking system in Malaysia. This will help customer or borrower of the loan to decide what type of bank credit and which commercial banks are the best for them to decide upon taking the loan. It will also save their time and money in choosing the best alternative. It will also save their time and money in choosing the best alternative as the calculations are tedious and complicated. In fact, the loan sometimes takes long period which ends up the total sum of money to be paid become enormous. Therefore, My eCredit Banking Apps (MECBA) V3 is the best solutions for your credit banking choices.